Ultrasonographic Classification of Achilles Tendon Ruptures as a Rationale for Individual Treatment Selection. (24th October 2011) - Amlang, Michael H.; Zwipp, Hans; Friedrich, Adina; Peaden, Adam; Bunk, Alfred; Rammelt, Stefan
Abstract : Purpose . This work introduces a distinct sonographic classification of Achilles tendon ruptures which has proven itself to be a reliable instrument for an individualized and differentiated therapy selection for patients who have suffered an Achilles tendon rupture. Materials and Methods . From January 1, 2000 to December 31, 2005, 273 patients who suffered from a complete subcutaneous rupture of the Achilles tendon (ASR) were clinically and sonographically evaluated. The sonographic classification was organized according to the location of the rupture, the contact of the tendon ends, and the structure of the interposition between the tendon ends. Results . In 266 of 273 (97.4%) patients the sonographic classification of the rupture of the Achilles tendon was recorded. Type 1 was detected in 54 patients (19.8%), type 2a in 68 (24.9%), type 2b in 33 (12.1%), type 3a in 20 (7.3%), type 3b in 61 (22.3%), type 4 in 20 (7.3%), and type 5 in 10 (3.7%). Of the patients with type 1 and fresh ASR, 96% (n = 47 ) were treated nonoperative-functionally, and 4% (n = 2 ) were treated by percutaneous suture with the Dresden instrument (pDI suture). Of the patients classified as type 2a with fresh ASR, 31 patients (48%) were treated nonoperatively-functionally and 33 patients (52%) with percutaneous suture with the Dresden instrument (pDI suture). Of the patients with type 3b and fresh ASR, 94% (n = 34 ) were treated by pDI suture and 6% (n = 2 ) by open suture according to Kirchmayr and Kessler. Conclusion . Unlike the clinical classification of the Achilles tendon rupture, the sonographic classification is a guide for deriving a graded and differentiated therapy from a broad spectrum of treatments.